2013
DOI: 10.1099/jmm.0.050708-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of carbapenemase-producing clinical isolates of Enterobacteriaceae in a teaching hospital, Japan

Abstract: We examined the molecular characteristics of 13 phenotypically confirmed carbapenemasepositive Enterobacteriaceae clinical isolates, including the relationships between plasmidmediated quinolone-resistance genes (qnr), 69-N-aminoglycoside acetyltransferase-encoding genes [aac(69)] and AmpC-encoding genes (pAmpC). Twelve isolates were bla IMP-1 positive (92.3 %), while one was bla IMP-11 positive (7.7 %). We detected qnr, aac(69) and pAmpC genes designated bla ACT-1 -like in 76.9 %, 100 % and 53.8 %, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…The authors described decreased expression of both ompF (5-fold) and ompC (500-fold) genes in resistant strains. The decrease in expression level of both major OM proteins was also recorded in the report published by Koyano et al (2013), Philippe et al (2015) and Jaskulski et al (2013). …”
Section: Discussionsupporting
confidence: 71%
“…The authors described decreased expression of both ompF (5-fold) and ompC (500-fold) genes in resistant strains. The decrease in expression level of both major OM proteins was also recorded in the report published by Koyano et al (2013), Philippe et al (2015) and Jaskulski et al (2013). …”
Section: Discussionsupporting
confidence: 71%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33][34] Koyano et al found that 13 (0.8%) of 1704 isolates from Tokyo were CPE, and mostly dominated by the IPM-1 gene (n = 12, 92.3%). 21 A study from another city in Japan showed that 20 CPE were included in two STs (ST2 and ST246), and 17 (85%) were bla OXA-23 type, 22 similar to results in Gunma University Hospital, Japan. 23 This is different from Vietnam, where NDM is dominant among CRE, similar to Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Various kinds of IMP enzyme were subsequently found in enteric and in glucose nonfermentative GNB species in other countries around the world [70][71][72]. To date, however, highly endemic GNB with IMP enzymes were only reported in Taiwan (bla IMP-8 ) [73] and in Japan (bla IMP-1 ) [74].…”
Section: Molecular Class B Carbapenemasesmentioning
confidence: 97%